2021
DOI: 10.3389/fcell.2021.639596
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HSP90AA1 Predicts the Risk of Breast Cancer Onset and Distant Metastasis

Abstract: AimWe aimed to develop and validate a comprehensive nomogram containing pre-treatment plasma HSP90AA1 to predict the risk of breast cancer onset and metastasis.MethodsWe assessed the expression of HSP90s in breast cancer patients using an online database. To verify the results, 677 patients diagnosed with breast cancer and 146 patients with benign breast disease between 2014 and 2019 were selected from our hospital and were divided into cancer risk and metastasis risk cohorts. We focused on HSP90AA1 to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Preliminary evidence suggests that the anticancer effects of sorafenib in HCC patients are related to these mechanisms. e results of previous studies have confirmed that SLC41A3, SEC61A1, LRP4, PPM1G, and HSP90AA1 play important roles in cancer progression [28][29][30][31][32][33][34][35][36][37][38][39]. SLC41A3 is a member of solute carrier family 41 and is involved in many cellular processes.…”
Section: Discussionmentioning
confidence: 77%
“…Preliminary evidence suggests that the anticancer effects of sorafenib in HCC patients are related to these mechanisms. e results of previous studies have confirmed that SLC41A3, SEC61A1, LRP4, PPM1G, and HSP90AA1 play important roles in cancer progression [28][29][30][31][32][33][34][35][36][37][38][39]. SLC41A3 is a member of solute carrier family 41 and is involved in many cellular processes.…”
Section: Discussionmentioning
confidence: 77%
“…In the course of this work, we discovered that heat shock protein 90-alpha (HSP90AA1) is the most highlighted gene in the network and based on the available data, HSP90AA1 is an evolutionary conserved protein which has a prominent role in processes such as DNA damage, inflammation and tumorigenesis. there is a considerable body of evidence that shows plasma levels of HSP90AA1 has clinical benefit in prediction of onset and risk of metastasis in breast cancer patients [ 51 ]. In the present work, it also became apparent that HSP90AA1 may has a role in prediction of response to therapy in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, HSP90AA1 was highly expressed in breast cancer tissues, and the low expression of HSP90AA1 indicated a good prognosis for patients with breast cancer. Moreover, a study by Liu et al ( 29 ) showed that pre-treatment plasma HSP90AA1 levels in combination with other markers could be an effective means of predicting breast cancer metastasis rates. MAPK14 is one of the four p38 MAPKs and a member of the MAP kinase family.…”
Section: Discussionmentioning
confidence: 99%